Tick saliva-induced programmed death-1 and PD-ligand 1 and its related host immunosuppression - Sajiki, Yamato; Konnai, Satoru; Ikenaka, Yoshinori; Gulay, Kevin Christian Montecillo; Kobayashi, Atsushi; Parizi, Luís Fernando; João, Benvindo Capela; Watari, Kei; Fujisawa, Sotaro; Okagawa, Tomohiro; Maekawa, Naoya; Logullo, Carlos; et al. (Scientific reports, 2021)
The tick Rhipicephalus microplus is a harmful parasite of cattle that causes considerable economic losses to the cattle breeding industry. Although R . microplus saliva (Rm-saliva) contains several immunosuppressants, any association between Rm-saliva and the expression of immunoinhibitory molecules, such as programmed death (PD)-1 and PD-ligand 1 (PD-L1), has not been described. In this study, flow cytometric analyses revealed that Rm-saliva upregulated PD-1 expression in T cells and PD-L1 expression in CD14 + and CD11c + cells in cattle. Additionally, Rm-saliva decreased CD69 expression in T cells and Th1 cytokine production from peripheral blood mononuclear cells. Furthermore, PD-L1 blockade increased IFN-γ production in the presence of Rm-saliva, suggesting that Rm-saliva suppresses Th1 responses via the PD-1/PD-L1 pathway. To reveal the upregulation mechanism of PD-1/PD-L1 by Rm-saliva, we analyzed the function of prostaglandin E 2 (PGE 2 ), which is known as an inducer of PD-L1 expression, in Rm-saliva. We found that Rm-saliva contained a high concentration of PGE 2 , and PGE 2 treatment induced PD-L1 expression in CD14 + cells in vitro. Immunohistochemical analyses revealed that PGE 2 and PD-L1 expression was upregulated in tick-attached skin in cattle. These data suggest that PGE 2 in Rm-saliva has the potential to induce the expression of immunoinhibitory molecules in host immune cells.